Air pollution and cardiovascular mortality with over 25 years follow-up: A combined analysis of two British cohorts. (February 2017) - Dehbi, Hakim-Moulay; Blangiardo, Marta; Gulliver, John; Fecht, Daniela; de Hoogh, Kees; Al-Kanaani, Zaina; Tillin, Therese; Hardy, Rebecca; Chaturvedi, Nish; Hansell, Anna L
Abstract: Background: Adverse effects of air pollution on cardiovascular disease (CVD) mortality are well established. There are comparatively fewer studies in Europe, and in the UK particularly, than in North America. We examined associations in two British cohorts with > 25 years of follow-up. Methods: Annual average NO2, SO2 and black smoke (BS) air pollution exposure estimates for 1991 were obtained from land use regression models using contemporaneous monitoring data. From the European Study of Cohorts and Air Pollution (ESCAPE), air pollution estimates in 2010–11 were obtained for NO2, NOx, PM10, PMcoarse and PM2.5 . The exposure estimates were assigned to place of residence 1989 for participants in a national birth cohort born in 1946, the MRC National Study of Health and Development (NSHD), and an adult multi-ethnic London cohort, Southall and Brent Revisited (SABRE) recruited 1988–91. The combined median follow-up was 26 years. Single-pollutant competing risk models were employed, adjusting for individual risk factors. Results: Elevated non-significant hazard ratios for CVD mortality were seen with 1991 BS and SO2 and with ESCAPE PM10 and PM2.5 in fully adjusted linear models. Per 10 μg/m 3 increase HRs were 1.11 [95% CI: 0.76–1.61] for BS, 1.05 [95% CI: 0.91–1.22] for SO2, 1.16 [95% CI: 0.70–1.92] for PM10 and 1.30 [95% CI: 0.39–4.34] for PM2.5, with largest effects seen in the fourth quartile of BS and PM2.5 compared to the first with HR 1.24 [95% CI: 0.91–1.61] and 1.21 [95% CI: 0.88–1.66] respectively. There were no consistent associations with other ESCAPE pollutants, or with 1991 NO2 . Modelling using Cox regression led to similar results. Conclusion: Our results support a detrimental long-term effect for air pollutants on cardiovascular mortality. Highlights: Adverse effects of air pollution on cardiovascular mortality are well established. There are comparatively fewer studies in the UK compared to North America. In two British cohort studies, we investigated associations between gases, particulates and cardiovascular mortality. Detrimental associations, non-statistically significant, between cardiovascular mortality and particulates were found.